The differences in the consumption of proteins, fats and carbohydrates in the diet of pregnant women diagnosed with arterial hypertension or arterial hypertension and hypothyroidism - Waksmańska, Wioletta (BMC Pregnancy Childbirth, 2020)
BACKGROUND: Excessive body weight induces the occurrence of arterial hypertension. The risk associated with irregularities during the perinatal period is increased in women with diagnosed hypothyroidism. Disorders of thyroid functions during pregnancy may cause higher body weight gains. The aim of this project was to determine the differences in the average daily intake of proteins, fats and carbohydrates in women with arterial hypertension and with hypothyroidism. METHODS: The control group (Group I) included healthy women. In this group, no complications during the course of pregnancy were observed and the delivery was on the due date. Group II was comprised of patients with arterial hypertension. Group III included patients with arterial hypertension, who were diagnosed with hypothyroidism before pregnancy. The women’s eating habits and dietary composition were analyzed based on a dietary assessment. RESULTS: Women with arterial hypertension (Group II) consumed the highest number of calories per day, while women with a normal pregnancy consumed the lowest amount of calories. The daily consumption of vegetable protein was similar in all study groups. The average daily consumption of fat, cholesterol and carbohydrates was the highest among women with diagnosed arterial hypertension. Women with arterial hypertension and hypothyroidism more frequently gave birth before the 38th week of pregnancy. The average daily intake of Arginine, Lysine, Methionine and Tryptophan was lower in the group of women with a normal pregnancy than in the two other groups. CONCLUSIONS: Excessive calorie intake causing significant body weight gain fostered the occurrence of arterial hypertension during pregnancy.